Need for Orthodontic Treatment Among Adults with Generalized Chronic Periodontitis - Sunil, Nurul Syamimi binti Mohd Azlan; M.D.S, Ravindra Kumar Jain; M.D.S, Revathi Duraisamy (The journal of contemporary issues in business and government, 2021)
One of the most common etiologic factors of periodontitis is malocclusion. Malocclusion as an etiologic factor to periodontitis is due to certain morphological traits of malocclusion which impede and prevent oral hygiene and self cleaning, which then leads to increased bacterial dental plaque accumulation. The aim of this study was to evaluate the need for orthodontic treatment among adults suffering from chronic periodontitis. This study included adults, both males and females who reported to Saveetha Dental College between June 2019 to March 2020. Inclusion criteria included adult patients between 18 to 40 years with chronic periodontitis. Patients outside the age range were excluded from the study. Around 86000 patient records were reviewed and analysed for the inclusion criteria and the following parameters were extracted; (i) patients’ gender, (ii) patient’s diet and (iii) presence of habits and (iv) orthodontic treatment need. Need for orthodontic treatment was measured using Dental Health Components of Orthodontic Treatment Need (DCH-IOTN). Data was recorded in Microsoft Office Excel (2013) and analysed using SPSS Software Version 26.0. Chi-square test was done to find out the association in need for orthodontic treatment between variables such as patient’s gender, diet and presence of habits. Significant level test was set at p<0.05. A total of 149 patients presented with chronic periodontitis and 63.4% of these patients needed orthodontic treatment (37.9% with need for orthodontic treatment and 25.5% with borderline need). 65.9% females and 62.4% males needed treatment. 96.1% of patients who presented with habits need orthodontic treatment. No statistically significant association was observed in gender and diet (p>0.05). Statistically significant association was found between patients with and without habits (p<0.05). Within the limits of this study, it was observed that the majority of patients with chronic periodontitis needed orthodontic treatment and treatment need was more common in females. Majority of patients with habits needed orthodontic treatment.